2015
DOI: 10.1016/j.jebo.2015.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Measuring time preferences: A comparison of experimental methods

Abstract: Eliciting time preferences has become an important component of both laboratory and field experiments, yet there is no consensus as how to best measure discounting. We examine the predictive validity of two recent, simple, easily administered, and individually successful elicitation tools: Convex Time Budgets (CTB) and Double Multiple Price Lists (DMPL). Using similar methods, the CTB and DMPL are compared using within-and out-of-sample predictions. While each perform equally well within sample, the CTB signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
125
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 178 publications
(153 citation statements)
references
References 33 publications
9
125
2
2
Order By: Relevance
“…We estimated all parameters via NLS for simplicity. In line with related papers (Andersen et al, 2008;Andreoni et al, 2015;Andreoni and Sprenger, 2012;Lührmann et al, 2015), we find a high level of heterogeneity across subjects for all parameters of…”
Section: Parameter Estimationsupporting
confidence: 92%
See 3 more Smart Citations
“…We estimated all parameters via NLS for simplicity. In line with related papers (Andersen et al, 2008;Andreoni et al, 2015;Andreoni and Sprenger, 2012;Lührmann et al, 2015), we find a high level of heterogeneity across subjects for all parameters of…”
Section: Parameter Estimationsupporting
confidence: 92%
“…However, this can be considered as a minor problem for our subsequent analysis due to the fact that experimental data provides vast evidence for the majority of subjects being risk averse for high and close to risk neutral, but still risk averse, for lower stakes Laury, 2002, 2005). Additionally, even though estimating a non-linear estimation equation does not account for the interval nature of the data, previous papers have shown that estimating an ICT regression model performed as a robustness check for the NLS regression produces equivalent 9 results (Andreoni et al, 2015;Lührmann et al, 2015). Moreover, the estimate for utility function curvature ↵ cannot be separately identified from the stochastic disturbance term ⌧ as explained below.…”
Section: Theoretical Framework and Estimation Strategiesmentioning
confidence: 97%
See 2 more Smart Citations
“…Incentivized work on methods for measuring time preferences has studied alternative ways to jointly measure a person's discount rate and utility function curvature (e.g. Andreoni and Sprenger (2012), Andreoni et al (2015), and Laury et al (2012)), but has ignored the possibility that the elicitation procedure used might a↵ect inferences about discounting even when restricted to the domain of dated rewards.…”
Section: Introductionmentioning
confidence: 99%